2020
DOI: 10.1177/0748730419898314
|View full text |Cite
|
Sign up to set email alerts
|

Two-Community Noisy Kuramoto Model Suggests Mechanism for Splitting in the Suprachiasmatic Nucleus

Abstract: Recent mathematical results for the noisy Kuramoto model on a 2-community network may explain some phenomena observed in the functioning of the suprachiasmatic nucleus (SCN). Specifically, these findings might explain the types of transitions to a state of the SCN in which 2 components are dissociated in phase, for example, in phase splitting. In contrast to previous studies, which required additional time-delayed coupling or large variation in the coupling strengths and other variations in the 2-community mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…One evidence for this proposition is the "splitting" of activity into two daily bouts which is observed in rodents maintained under artificial constant light (LL) for several days. The splitting phenomenon is considered the hallmark of the dual structure of the clock (Pittendrigh and Daan, 1976c;Oda and Friesen, 2002;Rohling and Meylahn, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…One evidence for this proposition is the "splitting" of activity into two daily bouts which is observed in rodents maintained under artificial constant light (LL) for several days. The splitting phenomenon is considered the hallmark of the dual structure of the clock (Pittendrigh and Daan, 1976c;Oda and Friesen, 2002;Rohling and Meylahn, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To simplify the model we have set the natural frequency of all oscillators to zero. Since any constant frequency can be rotated out by changing the frame of reference of the system, any constant average natural frequency can be chosen [23]. The equation for a single representative neuron is given by: Where D is the noise strength and W t is a standard Brownian motion.…”
Section: Methodsmentioning
confidence: 99%
“…An alternative explanation for the splitting phenomenon is given in Rohling and Meylahn (2020). They use a noisy Kuramoto model for the neurons operating in two communities, the left and right SCN.…”
Section: Communities Divided By the Right And The Left Scnmentioning
confidence: 99%
“…It has been shown that for long and short photoperiods the excitation-inhibition (E/I) balance in the SCN changes, when GABAergic connections between VL and DM in long-day photoperiod shifts from inhibitory to excitatory (Farajnia et al, 2014). The noisy Kuramoto model shows that a change in internal and external communication strengths within and between the communities, which changes the E/I balance of the SCN, may result in the SCN going from a stable synchronized state to an unstable state (Rohling and Meylahn, 2020). As this state is unstable, the SCN system tries to find a new (semi-)stable state, and in some circumstances this may be the split-state.…”
Section: Communities Divided By the Right And The Left Scnmentioning
confidence: 99%